12 trips in 12 months : make your own solo travel magic - Ruiz, Jennifer (Blackstone Publishing, 2024)
"Bestselling author Jen Ruiz takes readers on a trip around the globe in 12 Trips in 12 Months, defying societal expectations of what a woman is supposed to be--and empowering others to do the same. The year before her thirtieth birthday, Jen Ruiz decided to change everything. Despite being professionally accomplished and contributing to the world as an attorney at a nonprofit, she had yet to achieve the most important goal, according to society: becoming a wife and mother. So, after more ghostings than a graveyard, tired of dating apps and sitting in a windowless office, Jen embarked on an epic challenge to send her twenties out in style. Twelve months, twelve trips, no excuses. She started booking flights instead of swiping right, teaching English online to cover costs. Over the course of the year, Jen descended into a volcano in Iceland, volunteered at an elephant sanctuary in Thailand, called in sick to fly in a hot air balloon, and went scuba diving at an underwater museum in Mexico. She ended up taking twenty trips, almost double her original goal. In a moving and inspiring story, Jen invites readers along through the year wherein she decided to stop waiting for others and start living for herself, discovered the power of solo travel magic, challenged herself physically and emotionally, made meaningful connections...and learned that she could feel fulfilled and happy on her own." --